Muhammadiyah Sebagai Gerakan Islam, Dakwah dan Tajdid - Anugrah Giffari Syukri Rahman; Muhammad Hayat (PT. Nawa Edukasi Nusantara, 2025)
Founded in 1912 by K.H. Ahmad Dahlan, Muhammadiyah is one of the world's largest modernist Islamic organizations. Its enduring and massive influence for over a century is rooted in the synergy of three identity pillars: Islam, Da'wah, and Tajdid. This article analyzes how the integration of these pillars shapes Muhammadiyah's ideology and strategy, arguing that its strength lies in the dynamic dialectic among the three, rather than in any single one. As an Islamic movement, Muhammadiyah emphasizes the purification of creed (aqidah) through the slogan